Post-traumatic Perineal Pubic Rami Protrusion: A Simple Surgical Management - Voon Victor; Arshad Homa; Davis Ben (Journal of Orthopaedics, Trauma and Rehabilitation, 2014)
Although pubic ramus fractures are common, they usually heal without surgical intervention and result in little long-term disability. We herein present two cases of symptomatic malunion of pubic rami fracture, which was successfully treated with a simple and safe surgical technique. The patients' local symptoms resolved afterwards.